An Open-Source Code for the Calculation of the Effects of Mutual Coupling in Arrays of Wires and for the ASM-MBF Method - Christophe Craeye; Belen Andrés García; Enrique García Muñoz; Rémi Sarkis (International Journal of Antennas and Propagation)
A general description of mutual coupling in finite and infinite antenna arrays is provided and an open-source code is described for the analysis of mutual coupling in linear arrays of parallel dipoles. The ASM-MBF method is illustrated with the help of that code and it is shown that the method also can handle situations where eigenmodes are supported by the array: single machine precision is achieved with four Macro Basis Functions only.